Social workers' experiences of integrated case management for low-income individuals with mental illness in South Korea. (January 2019) - Sohn, Sunju; Jang, Soo Mi
Using a mixed methodology, the current level of integrated case management in South Korea was examined by exploring barriers to successful cooperation among agencies and quantifying networking activities in assisting low-income individuals with mental illness. Findings indicate the following: (1) struggling with limited resources while unrealistic expectations are imposed on mental health professionals, (2) poor collaboration and (3) the need for a functional organisation that plays a centralised role for a stronger and efficient integrated case management system. The results suggest the need to adopt a workable paradigm founded on a unified system within communities and a 'sharing' atmosphere.